2003
DOI: 10.1108/13673270310492930
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of knowledge management: a qualitative analysis

Abstract: This paper reports on the results of a qualitative study of middle managers’ perceptions of knowledge management (KM) implementation in NZ organizations. Data were collected in a survey of 71 attendees of a KM presentation. The data were analyzed using qualitative coding principles. Two core issues were examined – barriers and drivers of KM. Subcategories under barriers were primarily concerned with factors internal to the organization such as organizational culture, leadership, and education. Drivers were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 10 publications
1
68
0
2
Order By: Relevance
“…Based on the conclusions of several authors (Anantatmula and Kanungo, 2010, Bishop et al, 2008, Mullich, 2001, Quaddus and Xu, 2005, Mason and Pauleen, 2003, Xue et al, 2011, the main KM success factors reported are:…”
Section: Managerial and Social Issues In Kmmentioning
confidence: 99%
“…Based on the conclusions of several authors (Anantatmula and Kanungo, 2010, Bishop et al, 2008, Mullich, 2001, Quaddus and Xu, 2005, Mason and Pauleen, 2003, Xue et al, 2011, the main KM success factors reported are:…”
Section: Managerial and Social Issues In Kmmentioning
confidence: 99%
“…It is a problem to encourage the employees to share their knowledge because the knowledge is with them and is a sign of power to them (Grumbley, 1998). Due to the situation, Mason and Pauleen (2003) noted that this represents a formidable challenge for most managers. This paper addresses this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Lakshman (2009) argues sharply that the lack of leadership theory in information and knowledge management may be seen as a contributing factor to many of the well-documented problems caused by the lack of leadership in knowledge management (e.g. Güldenberg and Konrath, 2004;Singh and Kant, 2008;Mason and Pauleen, 2003;Chua, 2009) and information technology projects (e.g. Davenport and Prusak, 1997).…”
Section: Knowledge Management and Knowledge Leadershipmentioning
confidence: 99%